Constructing and De-constructing the "Good" Mothering Framework Online: a Pedagogical Analysis - Davide Cino (University of Bologna, 2020)
The present paper aims to take an interpretative stand towards some implicit and explicit pedagogical models informing the "good parenting" and, specifically here, "mothering" philosophy. After critically assessing the term "parenting", the contribution will stress how the social categories of "risk" and "protection" fostered the construction of a moral discourse on what it means to be a good parent and, specifically, a good mother, stressing potential problematic implications that these definitions come with. Informed by this framework, it will be highlighted the role played by the web, and specifically here parenting online platforms, in reinforcing or questioning the good parenting framework. Three different Italian platforms will then be discussed (the website Pianeta Mamma, the parenting forum Al Femminile, and the blog/social media accounts of Mammadimerda), looking at whether and how the subject(s) of the enunciation and the platforms' affordances contribute to the social construction of contrasting pedagogical models about parenting as an epistemic object.